The points are: (2,1) and (-2,-1) (5,6) and (3,10) (3,7) and (-2,5) Jul 21 | First Name from Baldwin Park, CA | 0 Answers | 1 Vote Mark favorite Subscribe Comment Comments 1)_ (2,1)&(-2,-1) As m = Y2-Y1 / X2-X1, then m = -1-1 / -2-2 m = -2 / -4 m = 1/2 Now we we either one points to find c from Y = mX + c putting the values of any points, we get 1 = (1/2)2 + c 1 = 1 + c now we get c = 0 So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then Y = 1/2X + 0 Hence Y = 1/2X Or 2Y = X 2)_ (3,7)&(-2,5) As m = Y2-Y1 / X2-X1, then m = 5-7 / -2-3 m = -2/-5 m = 2/5 Now we we either one points to find c from Y = mX + c putting the values of any points, we get 7 = (2/5)3 + c 29/5 = c now we get c = 29/5 So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then Hence Y = 2/5X + 29/5 Or 5Y = 2x =29 3)_ (5,6)&(3,10)As m = Y2-Y1 / X2-X1, then m = 10-6 / 3-5 m = 4 / -2 m = -2 Now we we either one points to find c from Y = mX + c putting the values of any points, we get 6 = (-2)5 + c 6 = -10 + c 6 + 10 = c c = 16 now we get c = 16 So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then Hence Y = -2X + 16 Or Y = 16 - 2x Jul 21 | First Name from Baldwin Park, CA Comment
1)_ (2,1)&(-2,-1) As m = Y2-Y1 / X2-X1, then m = -1-1 / -2-2 m = -2 / -4 m = 1/2 Now we we either one points to find c from Y = mX + c putting the values of any points, we get 1 = (1/2)2 + c 1 = 1 + c now we get c = 0 So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then Y = 1/2X + 0 Hence Y = 1/2X Or 2Y = X 2)_ (3,7)&(-2,5) As m = Y2-Y1 / X2-X1, then m = 5-7 / -2-3 m = -2/-5 m = 2/5 Now we we either one points to find c from Y = mX + c putting the values of any points, we get 7 = (2/5)3 + c 29/5 = c now we get c = 29/5 So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then Hence Y = 2/5X + 29/5 Or 5Y = 2x =29 3)_ (5,6)&(3,10)As m = Y2-Y1 / X2-X1, then m = 10-6 / 3-5 m = 4 / -2 m = -2 Now we we either one points to find c from Y = mX + c putting the values of any points, we get 6 = (-2)5 + c 6 = -10 + c 6 + 10 = c c = 16 now we get c = 16 So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then Hence Y = -2X + 16 Or Y = 16 - 2x Jul 21 | First Name from Baldwin Park, CA
Comments
As m = Y2-Y1 / X2-X1, then
m = -1-1 / -2-2
m = -2 / -4
m = 1/2
Now we we either one points to find c from
Y = mX + c
putting the values of any points, we get
1 = (1/2)2 + c
1 = 1 + c
now we get c = 0
So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then
Y = 1/2X + 0
Hence Y = 1/2X Or
2Y = X
2)_ (3,7)&(-2,5)
As m = Y2-Y1 / X2-X1, then
m = 5-7 / -2-3
m = -2/-5
m = 2/5
Now we we either one points to find c from
Y = mX + c
putting the values of any points, we get
7 = (2/5)3 + c
29/5 = c
now we get c = 29/5
So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then
Hence Y = 2/5X + 29/5 Or
5Y = 2x =29
3)_ (5,6)&(3,10)As m = Y2-Y1 / X2-X1, then
m = 10-6 / 3-5
m = 4 / -2
m = -2
Now we we either one points to find c from
Y = mX + c
putting the values of any points, we get
6 = (-2)5 + c
6 = -10 + c
6 + 10 = c
c = 16
now we get c = 16
So now we put the values of c and m in the equation Y = mX + c to get equation in slope intercept form, then
Hence Y = -2X + 16 Or
Y = 16 - 2x